Probing low-energy QCD with kaonic atoms at DAΦNE. (December 2020) - Tüchler, M; Zmeskal, J; Amirkhani, A; Amsler, C; Baniahmad, A; Bazzi, M; Bosnar, D; Bragadireanu, M A; Bühler, P; Cargnelli, M; Carminati, M; Clozza, A; et al.
Abstract: X-ray spectroscopy of kaonic atoms provides a versatile tool to study the strong interaction at low energies via a direct observation of its influence on the ground state of kaonic hydrogen atoms. The SIDDHARTA experiment provided precise results on the energy shift and width of the kaonic hydrogen 1s state induced by the strong interaction. To enable the extraction of the antikaon-nucleon scattering lengths a0 and a1, SIDDHARTA-2 aims to determine the energy shift and width in kaonic deuterium with precisions of 30 eV and 75 eV, respectively. This measurement is aggravated by the low kaonic deuterium X-ray yield and a high background environment and will only be possible by implementing a severe upgrade on the SIDDHARTA apparatus.